2020
DOI: 10.1371/journal.pone.0227441
|View full text |Cite
|
Sign up to set email alerts
|

The Brief Measure of Emotional Preoperative Stress (B-MEPS) as a new predictive tool for postoperative pain: A prospective observational cohort study

Abstract: Background Preoperative patients' vulnerabilities such as physical, social, and psychological are implicated in postoperative pain variability. Nevertheless, it is a challenge to analyze a patient's psychological profile in the preoperative period in a practical and consistent way. Thus, we sought to identify if high preoperative emotional stress, evaluated by the Brief Measure of Emotional Preoperative Stress (B-MEPS) scale is associated with higher postoperative pain levels and poor rehabilitation in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
0
11
1
2
Order By: Relevance
“…Prospective identification of these challenges, including the application of standardized cognitive and psychosocial assessments, can allow for appropriate preoperative referral, patient optimization, and future study of risk mitigation strategies [15,18,52,75,78,80,88]. To this end, various predictive tools for postoperative pain are being explored [88][89][90][91]. Patient-centered education and expectation management during the pre-admission phase of care are effective strategies for improving postoperative pain control, limiting postoperative opioid use, decreasing complications and readmissions, and increasing postoperative function and quality of life [15,18,[92][93][94][95][96][97][98].…”
Section: Patient Pain History Evaluation and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective identification of these challenges, including the application of standardized cognitive and psychosocial assessments, can allow for appropriate preoperative referral, patient optimization, and future study of risk mitigation strategies [15,18,52,75,78,80,88]. To this end, various predictive tools for postoperative pain are being explored [88][89][90][91]. Patient-centered education and expectation management during the pre-admission phase of care are effective strategies for improving postoperative pain control, limiting postoperative opioid use, decreasing complications and readmissions, and increasing postoperative function and quality of life [15,18,[92][93][94][95][96][97][98].…”
Section: Patient Pain History Evaluation and Educationmentioning
confidence: 99%
“…Validated health literacy assessments have been applied to surgical populations [ 83 , 84 , 85 , 86 , 87 ]. Prospective identification of these challenges, including the application of standardized cognitive and psychosocial assessments, can allow for appropriate preoperative referral, patient optimization, and future study of risk mitigation strategies [ 15 , 18 , 52 , 75 , 78 , 80 , 88 ]. To this end, various predictive tools for postoperative pain are being explored [ 88 , 89 , 90 , 91 ].…”
Section: Pain Management and Opioid Stewardship Across The Periopementioning
confidence: 99%
“…The questionnaire used to assess pain catastrophising was the pain catastrophising scale (PCS) [94]. The questionnaires used to assess stress were the DASS-21 [67], the Perceived Stress Scale (PSS) [68], 4DSQ [125]and the Brief Measure of Emotional Preoperative Stress (B-MEPS) [138]. The questionnaires used to assess sleep were the Medical Outcomes Study Sleep Scale (MOS) [3], the Basic Scale of Insomnia Complaints and Quality of Sleep (BaSIQs) [2], and the Insomnia Severity Index (ISI) [87].…”
Section: Psychological Measuresmentioning
confidence: 99%
“…Additionally, it is important to note that, not only nociceptive stimulus from tissue trauma, but also other factors such as socio-culture and individual characteristics may affect subjective pain perception. Wolmeister and colleagues [ 26 ] demonstrated that individuals with elevated preoperative emotional stress present higher postoperative pain levels. Person and colleagues [ 27 ] suggested that women with high stress-coping abilities have a better outcome in general well-being than women with low stress-coping capacity.…”
Section: Discussionmentioning
confidence: 99%